The Holocaust in Vilkaviškis County: the Fate of Pilviškiai Jewish Community in 1941 - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2024)
Until summer 1941, Pilviškiai was one of the important locations populated with Litvaks (Lithuanian Jews) in Užnemunė (the area on the left bank of the River Nemunas) and in Vilkaviškis County. From the 18th century, Jews in Pilviškiai had engaged in their traditional businesses and culture and between the middle of the 19th century and beginning of the 20th century, were the biggest population group in the city. They were well known as trade intermediaries between the Russian governorates and Germany. Sales mediation conditions deteriorated after WW1, when the political map of Eastern and Central Europe changed and Poles occupied Vilnius. However, ties with Germany continued to be close. In addition to trade, the Jews of Pilviškiai focused both their energy and financial resources on local industry, electric power stations, agriculture, and activities for the modernisation of the town. An exclusive phenomenon of Pilviškiai was the model Kibbutz. After the Jews had gained experience with the Kibbutz there, they moved to Arab populated Palestine to lay the foundation for the Jewish state. Many Jews from Pilviškiai emigrated to the USA. At the beginning of the1940s, around 100 Jews drawn from the Suwałki Region joined the Jewish community of Pilviškiai. In 1940, therefore, the population of Jews in Pilviškiai was over 1,000. During the first occupation of Bolsheviks (1940−1941), they suffered as much as the Lithuanians did and were also deported. The majority of local Germans were repatriated to Germany in 1941. At the outbreak of the war between Germany and the Soviet Union, the Catholic Church and some of the Jewish buildings in Pilviškiai were burned down. As a result, a significant number of Jews moved to rural areas, to the farms. On 23 June 1941, the Wehrmacht army entered Pilviškiai; on the same day a German anti-Semite shot the Jew, Hertcel Lurija. Of the arrested Soviet activists, at least two were Jewish – and survived the Nazi occupation. Discriminatory clauses were published on 28 June. The Nazis did not succeed in using local protection units (national activists) for the persecution of Jews; these units had been formed at the beginning of the war and the June uprising to protect the residents and their property against demoralised Red Army soldiers. As a result the military commandant of Pilviškiai, Kramer, and the troops of Tilsit operational unit had to avail of the help of a random pro Nazi collaborator. It was planned to kill all the Jewish men of Pilviškiai (and those elsewhere in Vilkaviškis County) as early as July. However, the Nazi operational forces were prevented from carrying out their plan, because the military authorities used Jews as workers required by the Wehrmacht (for making clothes, footwear). The Jew Laibel Ziberg managed the reconstruction of the Tigras Factory (or one of its workshops). The Jews were allowed to form a council consisting of four men. The regime softened its attitude towards them, the situation improved (food was supplied and there were no further tortures). However, it deteriorated again with the arrival of the new commandant Martin. There wasn’t a typical ghetto in Pilviškiai. The men, who were condemned to death, were kept in a barn for two days. Most of the Jewish men were shot on 29 August 1941 near Baltrušiai Village (2–2.5 km from Pilviškiai) (300–350 dead, of which around 20 girls who belonged to the Comsomol organisation) and women and children – on 15 September (550–600 people). It was mainly German killers, brought from Vilkaviškis, who carried out the mass execution of Jewish people. After the massacre, only those Jewish workers who produced for the Wehrmacht remained alive (around 80 people, perhaps members of their family), and a score or so of those hiding in the homes of local residents. Groups of Jews from Pilviškiai were also drawn to the ghettos of Vilkaviškis, Marijampolė, and Kaunas as well as other places of detention. There is evidence that on 14 November 1941, Germans killed 40 Jews in a location 4 km from Pilviškiai. It is hard to be certain, but, between 1941 and 1945, about 10% of the 1940-strong Jewish community members of Pilviškiai managed to escape (with those who moved east from the German-Soviet frontline). The criminal files of local men drawn into the Holocaust are extensive, yet very controversial; they contain a number of forged and unreliable testimonies. The Soviet repressive machine often passed stricter sentences for “treason”, detention of soviet activists or Red Army soldiers, etc. than for involvement in the massacre of Jews. The majority of the 30–40 residents of Pilviškiai who were forced into the Nazi practices were guards of the persecuted Jews and only some of them tortured and killed their neighbour Jews. A more detailed reconstruction of the Jewish Holocaust in Pilviškiai (and in Užnemunė) could be possible by examining the sources on the activities of the Tilsit operational squad in 1941 that are to be mostly found in archives abroad.